Efektivitas Acceptance and Commitment Therapy (ACT) dalam Mengatasi Depresi dan Kecemasan Serta Meningkatkan Kualitas Hidup - Noraini, Noraini; Putri, Yossie Susanti Eka; Panjaitan, Ria Utami (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to analyze the effectiveness of acceptance and commitment therapy (ACT) on the quality of life in patients with depression and anxiety. The research method used is a systematic review through searching for articles adapted to the formulation of research questions using the PICO formula in online databases (PubMed, Scopus, and ScienceDirect). The articles reviewed met the inclusion criteria and the articles were published between 2010 and 2023. The search results found 8 articles with research showing that acceptance and commitment therapy (ACT) is an effective intervention for reducing symptoms of depression, both face-to-face and Web-based. In conclusion, to improve the quality of life of depressed patients with anxiety, therapy can be carried out on these individuals by carrying out acceptance and commitment therapy (ACT). Keywords: Depression, Anxiety, Quality of Life, ACT therapy